A Sociorhetorical Analysis of Clark H. Pinnock's Hermeneutical Approach to Biblical Materials, with Particular Attention to the Role of Religious Experience - Robinson, Peter S. (Université Saint-Paul / Saint Paul University, 2013)
The goal of this thesis was to use sociorhetorical investigation (SRI) to study religious experience in three books by Canadian, evangelical scholar Clark H. Pinnock: Biblical Revelation (1971), The Scripture Principle (1984), and Flame of Love (1996)—with reference to The Scripture Principle (2006). I focused on the analysis of three essential textures layered within his texts: the inner textual, intertextural, and ideological textures. (The sociocultural texture was subsumed under intertexture.) Through inner textural analysis, we tracked eight lemmas. They provided evidence of Pinnock’s movement from biblical inspiration as a grammatical event, to inspiration as a dynamic, cultural work of God within human language, to the imperative of a spiritually-discerning listening to God’s will whereby subjective truth (personal and corporate experience as recorded in tradition) shares validity with the external truth of the Scriptures. Intertextural evidence, using the rhetorical feature of “topoi” (seats of argumentation), provided evidence of Pinnock’s shift toward mystery, relations within the Trinity, and the mobility of the Spirit; his reasoning from a nexus that was relational and sensitive to experience; then his turn to a religious understanding of Spirit-infused theology stressing the rhetorical edges of presence, power, love, and universal redemption. Analysis of the ideological texture led us to focus on Pinnock’s form of theological reflection, and identified how his understanding of “object” changed, from that of something scientifically verified to that of something truly there that nevertheless could be understood by an interpreting subject. As a result, I discovered evidence of a significant shift in his understanding of God. Yet I also discovered that he understood that his new horizons had already been charted by the historic church. For him, the Spirit authenticates genuine experience within the medium of apostolic teaching. SRI has proven to be a fitting analytic. Though it is still relatively new and in development, it provided a “thick” reading of Pinnock’s theological reflections, allowing us to minimize bias or foregone conclusions, and ensuring a solid gathering of data. SRI has opened up a methodological resource for the broader realm of theological investigation.
Keywords: sociorhetorical investigation; human spirituality; spirituality; religious experience; Clark H. Pinnock; Vernon K. Robbins; L. Gregory Bloomquist; classic Christianity; historic Christianity; anthropological starting-point; anthropocentric spirituality